Influence of organ donor attributes and preparation characteristics on the dynamics of insulin secretion in isolated human islets - Henquin, Jean‐Claude (Physiol Rep, 2018)
In vitro studies of human pancreatic islets are critical for understanding normal insulin secretion and its perturbations in diabetic β‐cells, but the influence of islet preparation characteristics and organ donor attributes in such experiments is poorly documented. Preparations from normal donors were tested with a standardized protocol evaluating dynamic insulin secretion induced by glucose, tolbutamide, and cAMP (forskolin). Secretion rates, normalized to insulin content (fractional insulin secretion), were analyzed as a function of preparation and donor characteristics. Low purity (25–45%) of the preparation (n = 8) blunted the first phase of insulin secretion induced by glucose or tolbutamide and increased basal secretion, resulting in threefold lower stimulation index than in more pure (55–95%) preparations (n = 43). In these more pure preparations, cold ischemia time (1–13 h) before pancreas digestion did not impact insulin secretion. Islet size (estimated by the islet size index) did not influence the dynamics of secretion, but fractional insulin secretion rates were greater in large than small islets, and positively correlated with islet size. Age of the donors (20–68 years) had no influence on islet size and insulin content or on dynamics and amplitude of insulin secretion, which were also similar in islets from male and female donors. In contrast, islet size and islet insulin content (normalized for size), and basal or stimulated insulin secretion positively correlated with Body‐Mass Index (19–33). These results contradict previous reports on the impact of donor age and islet size and point to possible confounding effects of donor BMI in insulin secretion studies with isolated human islets.